Fatty acid metabolism is involved in both retinal physiology and the pathology of retinal vascular diseases. (August 2022) - Umetsu, Araya; Furuhashi, Masato; Watanabe, Megumi; Ohkawa, Ei; Tsugeno, Yuri; Suzuki, Soma; Itoh, Kaku; Ida, Yosuke; Hikage, Fumihito; Ohguro, Hiroshi
Highlights: Vitreous free fatty acids levels were elevated in the retinal vascular diseases. Vitreous free fatty acids levels were not correlated with their serum levels. Among several FABPs, FABP4 is commonly expressed within the retina in most species. FABP4 appears to have significant roles in pathophysiology of retinal vascular diseases. Abstract: To study the pathophysiological roles of the fatty acid-binding proteins (FABPs) within the retina, we performed; (1) immunolabeling of human retinas, wild type (WT) rat and mouse retinas, rat models for diabetic retinopathy (DR) and retinitis pigmentosa (RP) with anti-FABP3, FABP4, FABP5, FABP7, FABP8 and FABP12, (2) electroretinogram (ERG) measurements of WT and FABP4-deficient ( Fabp4 -/- ) mice, (3) ELISA or gas chromatography measurements of plasma (P-) and vitreous (V-) levels of FABP4 and vascular endothelial growth factor A (VEGFA), and fatty acids (FAs) from patients with retinal vascular disease (RVD) including proliferative DR (PDR, n  = 30) and retinal vein occlusion (RVO, n  = 18) and non-RVD ( n  = 18). Within the human retina, diverse expressions of FABP3, FABP4, FABP7 and FABP8 were identified. In contrast, positive immunoreactivities toward only FABP4 and FABP12 were detected in the cases of rat and mouse retinas, and interestingly, the FABP4 labeling patterns for the WT, DR and RP rat retinas were different. The ERG amplitudes of Fabp4 -/- mice were enhanced compared with those of WT mice. The concentrations of V-FABP4, V-VEGFA and total FAs were significantly higher in RVD patients than in non-PDR patients ( P < 0.05). The V-FAs levels of each were significantly and positively correlated with V-FABP4 and V-VEGFA, although no significant correlation between vitreous (V-) and plasma (P-) FABP4, VEGFA and FAs were detected. The current study reveals that V-FAs appear to have significant roles in both retinal physiology as well as the pathogenesis of RVD with FABP4, which is commonly expressed within the retina in most species.